The effectiveness and safety of short‐contact dithranol therapy in paediatric psoriasis: a prospective comparison of regular day care and day care with telemedicine. (February 2014) - Oostveen, A.M.; Beulens, C.A.; van de, P.C.M.; de, E.M.G.J.; Seyger, M.M.B.
Summary Background Evidence on the effectiveness and safety of short‐contact dithranol therapy in paediatric psoriasis is sparse and based only on retrospective data. The best results are achieved in a time‐consuming day‐care setting. Objectives To study prospectively the effectiveness and safety of short‐contact dithranol therapy in paediatric psoriasis. In addition, the effectiveness, safety, duration of treatment and number of visits between regular day care and day care with telemedicine were compared. Methods Data were collected from the prospective observational Child‐CAPTURE registry of children with psoriasis. Effectiveness was measured as the mean percentage improvement in Psoriasis Area and Severity Index (PASI). Safety was assessed by recording adverse events. The number of visits and duration of treatment were reported. Results For all patients a mean percentage reduction in PASI score of −69·3% was found, with no significant differences between regular day care and day care with telemedicine. The only adverse event reported was irritation of the skin. Neither the frequency of irritation during treatment nor the mean duration of treatment significantly differed between the two groups. Patients with telemedicine had significantly fewer visits. Conclusions This first prospective observational study demonstrates that short‐contact dithranol therapy in paediatric psoriasis is effective and safe. Regular day care and day care with telemedicine are equally effective. Telemedicine can be of additional value as it is less time consuming. We hope it will therefore make dithranol treatment appropriate for a larger number of children with psoriasis.